Persulfate Process Activated by Homogeneous and Heterogeneous Catalysts for Synthetic Olive Mill Wastewater Treatment - Eva Domingues (MDPI AG, 2021)
Wastewaters from the olive oil industry are a regional environmental problem. Their phenolic content provides inherent toxicity, which reduces the treatment potential of conventional biological systems. In this study, Sulfate Radical based Advanced Oxidation Processes (SRbAOPs) are compared with advanced oxidation processes (namely Fenton’s peroxidation) as a depuration alternative. Synthetic olive mill wastewaters were submitted to homogeneous and heterogeneous SRbAOPs using iron sulfate and solid catalysts (red mud and Fe-Ce-O) as the source of iron (II). The homogenous process was optimized by testing different pH values, as well as iron and persulfate loads. At the best conditions (pH 5, 300 mg/L of iron and 600 mg/L of persulfate), it was possible to achieve 39%, 63% and 37% COD, phenolic compounds and TOC removal, respectively. The catalytic potential of a waste (red mud) and a laboratory material (Fe-Ce-O) was tested using heterogenous SRbAOPs. The best performance was achieved by Fe-Ce-O, with an optimal load of 1600 mg/L. At these conditions, 27%, 55% and 5% COD, phenolic compounds and TOC removal were obtained, respectively. Toxicity tests on A. fischeri and L. sativum showed no improvements in toxicity from the treated solutions when compared with the original one. Thus, SRbAOPs use a suitable technology for synthetic OMW.